Analysis of Competitiveness with Online Marketing Tools in Hungary - Katalin Tari; Nikolett Mihály (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
In the world of marketing, innovative solutions and new development opportunities will always come into play. They play of the major factor in improving the competitiveness and for consumers needs as well. The aim of the study is to examine and compare the efficiency and effectiveness measurement of the online campaigns. At first, this study is arising the theoretical approaches and then points to the practical application differences and also wants to rank the effectiveness of online. The currently used Hungarian online measures (rate/index) are explained in this study by using the available practical literature. The in-depth interviews will be conducted with the consent of online shop managers and leader professionals of creative and advertisement agencies. Procession of the practical literature will include the online advertising methods ranked by the CPM (Cost per 1000 Impression) will imply the effectiveness of ads. Our research methodology followed qualitative strategy, on the base of content analyses of in-depth interviews of online experts (N=7). We recorded the conversation and then we transcribed the data. Our questions were structured. The questioning went between 10 March 2016 and 18 May. 7 persons have taken part in the research, regarding to their profession they were mid, - or top managers and had at least 4 maximum 15 years of experience. Regarding to their activities, there are who is planning, leading and following up marketing and/or creative campaigns – together with analyses – or with full-service of web shop, online legal advising, retargeting and optimization services. Each interviewee serves the business-to-business trade. Furthermore our aim is to present the Hungarian online advertising trends in 2016. This indication will show the effectiveness of different marketing tools, also the reach of online experts, which is a tool in increasing competitiveness. This research will point out the possible measuring methods and indications, which allows the integrated testing of performance on different channels.
Keywords: A32; 330; efficiency; efficiency measurement; online marketing; competitiveness